The best interests of the child in medically assisted reproduction: A moral-constitutional overview - Panagopoulou - Koutnatzi, Fereniki (Ηθική. Περιοδικό φιλοσοφίας, 2021)
The infinite and constantly developing options of medically assisted reproduction (MAR) reasonably raise the issue of its permitted range. Proponents of human rights fight for the strengthening of the reproductive right, the access to it by even more people, such as single parents, same-sex couples, elderly women, HIV carriers etc. Still concerning, however, is the fact that the defenders of human rights often forget the rights of the fetus or the child, which cannot be expressed with the same intensity. In the framework of the present study, we investigate the true interests of the child in MAR, in relation to the reproductive right in the light of some borderline cases.